Primary prevention of cardiovascular disease: new guidelines, technologies and therapies. Issue 11 (17th June 2013) - Nelson, Mark R; Doust, Jennifer A
Abstract: A trend in primary prevention of cardiovascular disease (CVD) has been a move away from managing isolated risk factors, such as hypertension and dyslipidaemia, towards assessment and management of absolute CVD risk. In Australian guidelines, absolute CVD risk is calculated as the probability of a stroke, transient ischaemic attack, myocardial infarction, angina, peripheral arterial disease or heart failure occurring within the next 5 years. Absolute CVD risk should be regularly assessed in patients aged 45 years or older (35 years or older in Aboriginal and Torres Strait Islander people) using the Australian absolute CVD risk calculator (http://www.cvdcheck.org.au ). For patients currently taking a blood pressure (BP)‐lowering or lipid‐lowering agent, pretreatment values should be used to calculate risk. Patients at high absolute risk of CVD (> 15% over 5 years) should be treated with both BP‐lowering and lipid‐lowering agents, unless contraindicated or clinically inappropriate. For patients at moderate absolute risk of CVD (10%–15%) treatment with a BP‐lowering and/or a lipid‐lowering agent should be considered if the risk remains elevated after lifestyle interventions, BP is ≥ 160/100 mmHg, there is a family history of premature CVD, or the patient is of South Asian, Middle Eastern, Maori, Pacific Islander, Aboriginal or Torres Strait Islander ethnicity. BP measurements taken using an oscillometric device can be used to approximate mean daytime ambulatory BP.